Reliability and Validity of the Pain Self-efficacy Questionnaire in Simplified Chinese Version - Zhongfei BAI; Mengjian QU; Enqi DING; Qinghe ZHAO; Weili XIA; Tian SHU; Jiani LU (康复学报)
Objective:To test the reliability and validity of the pain self-efficacy questionnaire in simplified Chinese version(SC-PSEQ)in patients with low back pain.Methods:A total of 86 participants with low back pain were recruited in four hospitals. They independently completed the simplified Chinese version of pain self-efficacy questionnaire, Numeric Pain Rating Scale, Oswestry Disability Index, Roland-Morris Disability Questionnaire, 36-Item Short Form Health Survey.Results:The average score of all the participants was(46.29±11.16),which was statistically different from the median score of SC-PSEQ(t=13.535,P<0.001).In addition,10.47%of them were scored with the maximum possible score. Factor analysis indicated that the SC-PSEQ was unidimensional and 61.56%variance could be explained with the one factor. The questionnaire also had high level of internal consistency(Cronbach's α=0.929)and test-retest reliability(ICC=0.852,P<0.001).Conclusion:The SC-PSEQ has consistent level of measurement properties with the original English version. Appropriate adjustment for its items may reduce the extent of ceiling effect.